3D Simulation of Fin Geometry influence on Corner effect in Multiﬁn Dual and Tri-gate SOI-FinFETs - A.N. Moulai Khatir; A. Guen-Bouazza; B. Bouazza (Institute of Advanced Engineering and Science, 2014)
In this work the corner effect sensitivity to fin geometry variation in multifin dual and tri-gate SOI-FinFETs is studied through a commercial, three-dimensional numerical simulator ATLAS from Silvaco International. These devices are compatible with conventional silicon integrated circuit processing, but offer superior performance as the device is scaled into the nanometer range. This study aims wider to use multiple fins between the source and drain regions. The results indicate that for both multifin double and triple gate FinFETs, the corner effect does not lead to an additional leakage current and therefore does not deteriorate the SOI-FinFET performance. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4668